La necesidad de que la autonomía descentralizada no genere conflicto para el desarrollo integral del país - Mogrovejo Baca, Luis Alonso (2023)
Decentralization is a process established in the Political Constitution of Peru, which makes it possible to extend the representation of the unitary state in the country throughout its territory. The constitutional history of Peru, there have been attempts to implement different forms of political organization. During the 19th century, an attempt was made to establish a unitary government, despite the great conflicts of representation that still existed due to the remnants of Spanish dependence. In view of this, there was a proposal to convert it into a federated state, but it did not have a great impact, so that to date it has been consolidated as unitary, decentralized and deconcentrated. In spite of this, Peru is a very politically divided country and we have more than a thousand burgomasters, considering that the territory is only divided into twenty-four regions and one constitutional province. In this sense, the present research work seeks to analyze a way to synthesize the number of provincial and district municipalities through historical methods; in addition, to establish an organizational hierarchy for each level of government, with the purpose of achieving an integral development of the country with a sociological and functional legal method, which is the main objective of this process.